1995
DOI: 10.1111/1523-1747.ep12316695
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus Vulgaris and Pemphigus Foliaceus Sera Show an Inversely Graded Binding Pattern to Extracellular Regions of Desmosomes in Different Layers of Human Epidermis

Abstract: We analyzed the location of binding sites for pemphigus vulgaris (PV) antigen and pemphigus foliaceus (PF) antigen in the human epidermis using serum samples obtained from three patients with PV and three patients with PF. Confocal laser scanning microscopy, immunofluorescent examination of ultrathin cryosections, and immunoperoxidase electron microscopy demonstrated discontinuous dots along the epidermal cell surfaces. Immunogold electron microscopy of ultrathin cryosections showed specific binding of PV and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 38 publications
5
55
0
Order By: Relevance
“…We have established previously that different Dsc isoforms can be located in the same individual desmosomes (20,21), and the same probably is true for Dsgs (59). We detected no patterned arrangement of the different Dsc isoforms in epidermal desmosomes, although the immuno-gold labeling technique may not have sufficient resolution to resolve such a pattern (21).…”
Section: Discussionsupporting
confidence: 48%
“…We have established previously that different Dsc isoforms can be located in the same individual desmosomes (20,21), and the same probably is true for Dsgs (59). We detected no patterned arrangement of the different Dsc isoforms in epidermal desmosomes, although the immuno-gold labeling technique may not have sufficient resolution to resolve such a pattern (21).…”
Section: Discussionsupporting
confidence: 48%
“…It has been suggested (27)(28)(29)(30) that the distribution and expression levels of Dsg1 and Dsg3 might account for the characteristic distribution of lesions. For example, Dsg3 is expressed throughout the oral mucosa, whereas it is only expressed in the basal and immediate suprabasal layer of the epidermis (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…19 iv) To visualize the desmoglein localization pattern in human epidermis, autoantibodies from patients with PV and PF have been applied. 15,20 In these studies, either whole sera of PV and PF patients were used without characterization of the autoantibody profile 20 or IgG fractions were used after immunosabsorption with recombinant Dsg extracellular domains fused to the Fc portion of human IgG. 15 More recently, it has been suggested that immunoabsorption using this fusion protein containing the extracellular domain of desmogleins is not entirely specific.…”
mentioning
confidence: 99%